Cellular fatty acids of Capnocytophaga species. - Dees, S B (1982)
The cellular fatty acid composition of 18 clinical isolates and 4 reference strains of Capnocytophaga species (Capnocytophaga ochracea, Capnocytophaga gingivalis, and Capnocytophaga sputigena) was determined by gas-liquid chromatography. The fatty acid profiles of the 22 cultures were essentially identical and were characterized by major amounts (60% or greater) of a saturated, iso-branched-chain, 15-carbon acid (13-methyl-tetradecanoate) and the presence of two relatively uncommon saturated, iso-branched, 3-hydroxy acids (13-methyl-3-hydroxy-tetradecanoate and 15-methyl-3-hydroxy-hexadecanoate). The presence and relative amounts of these acids distinguish Capnocytophaga spp. from other gliding bacteria.